Carlos Trincheiras: a Look at the Legacy of the Portuguese Choreographer in Brazil - Norton Dias, Teresa (2021)
We wanted to pay homage, recalling, in a year in which Portugal-Brazil relations (2013) were celebrated, the Portuguesechoreographer who, once established in Brasil, in August 1979, lost himself in the dormant form of the memories thateach guard of the your legacy. We tried to remember his stay in that country, which have not gone unnoticed in the cityof Curitiba, state of Paraná, where he settled. The Guaíra Theater was the headquarters of his work, giving new impetusto a group of ballet dancers who, until then, were part of the Teatro Guaíra Foundation's Ballet, helping and supportingtheir growth in number and in experience, instilling a new dynamic and work philosophy, in which the technical rigor did notintimidate the artistic interpretation of those who danced.